The 2011 Tohoku-oki tsunami-induced sediment remobilization on the Sendai shelf, Japan, from a comparison of pre- and post-tsunami surface sediments - Ken Ikehara (Nature Portfolio, 2021)
Abstract Tsunamis are generally considered to disturb the seafloor, rework surface sediments, and change seafloor environments. However, the response of the seafloor to such extreme wave events has not been fully elucidated. Herein, we compare the surface sediments before and after the 2011 Tohoku-oki tsunami on the Sendai shelf and demonstrate that both sandy and muddy sediments were significantly reworked on the shelf. Muddy sediments (> 10 cm thick) were redeposited as graded mud with no or little bioturbation, characterizing the offshore muddy tsunami deposit, while well-sorted sand was found as the sandy tsunami deposit. This redeposited layer could also be retained in the shelf mud sequence. The results imply that the high friction velocity of the tsunami wave and its long-term effect on Sendai Bay might contribute to the large sediment reworking. Part of the resuspended mud moved offshore to the slope area as turbidity currents. Thus, the tsunami is an important mechanism not only for shelf sedimentation but also for deep-sea sedimentation along active plate margins. The detection of 134Cs derived from the Fukushima Daiichi Nuclear Power Plant accident in the redeposited mud indicates that the suspended shelf water state was maintained for some days after the tsunami.